Low frequency energy harvesting using piezoelectric materials - Kang, Yin Teng (2015)
The scarcity of energy sources such as fossil fuels and the increasing environmental mindfulness have driven the demand for energy harvesting. While countless innovative techniques have been implemented to scavenge ambient energy, there is a forgotten source of energy that deserves more attention than it is currently garnering. Human power can be a viable power source for electronics which are consuming less power these days (Jansen & Stevels, 1999). This final year project intends to build on the convenience and availability of human power via the design of a handheld piezoelectric harvester. The design employed comprises a triple-tiered cantilevered Macro-Fiber Composite (MFC) harvester. Numerous stages of experiments conducted with varied gap distances, materials and tip masses have led to conclusions drawn on the parameters of a cantilevered design. It was decided that within an acceleration range of 0.4g to 0.9g, a system with varied gap distances between beams would produce more voltage output as compared to its counterpart with evenly spaced gaps. Additionally, the range of frequencies and accelerations for human hand-shaking were also experimentally determined to be 1.0Hz to 5.5Hz and 0.5g to 5.5g respectively. Pertaining to the analysis of materials, bimorph strips were discovered to be unsuitable for impact-driven harvesters as their stiffness rendered them fragile. MFCs were proven to be superior, but insufficient in strength to withstand a cantilevered system with an input force of 0.25N.